Knowledge and Treatment Complience among Hypertensive Patient Attending in a Tertiary Level Hospital, Kathmandu - Rai, Lalita; Gautam, Roshani (Tribhuvan University Journal, 2023)
Globally, non-communicable diseases are increasing in trend in both developed and developing countries. Hypertension is considered as one of the main cardiovascular disease which is responsible for life threatening complications and premature death. Knowledge and treatment adherence on hypertension are important to control hypertension and prevent long term complications. A descriptive cross-sectional research design was used to find out the knowledge and treatment compliance among hypertensive patients in a Tertiary level hospital. Non-probability sampling technique was used to collect data from 427 people with hypertension through in-person interview. Data analysis was done by using SPSS version 16. Descriptive and inferential statistics was calculated. Out of 427 study participants, half (46.1%) were belong to more than 60 years of age with mean age was 57.30, SD ±12.134, half (55.3%) of the participants were female, 30.44% have positive family history of hypertension and 62.30% had comorbidity. Regarding knowledge on hypertension, more than half (57.8%) of the participants had inadequate knowledge related to hypertension. Overall treatment compliance was poor (6.1%). There was no significant association between knowledge and treatment compliances. So, it is recommended to conduct awareness program related to risk factors and modification of life-style of the people.